Cefditoren in upper and lower community-acquired respiratory tract infections - Francisco Soriano; María-José Giménez; Lorenzo Aguilar (Dove Medical Press, 2011)
Francisco Soriano1, María-José Giménez1,2, Lorenzo Aguilar1,21PRISM-AG, Madrid, Spain; 2Microbiology Department, School of Medicine, University Complutense, Madrid, SpainAbstract: This article reviews and updates published data on cefditoren in the evolving scenario of resistance among the most prevalent isolates from respiratory tract infections in the community (Streptococcus pyogenes, Haemophilus influenzae, and Streptococcus pneumoniae). By relating the in vitro activity of cefditoren (in national and multinational surveillance and against isolates with emerging resistant genotypes/phenotypes) to its pharmacokinetics, the cefditoren pharmacodynamic activity predicting efficacy (in humans, animal models, and in vitro simulations) is analyzed prior to reviewing clinical studies (tonsillopharyngitis, sinusitis, acute exacerbations of chronic bronchitis, and community-acquired pneumonia) and the relationship between bacterial eradication and clinical efficacy. The high in vitro activity of cefditoren against the most prevalent respiratory isolates in the community, together with its pharmacokinetics (enabling a twice daily regimen) leading to adequate pharmacodynamic indexes covering all S. pyogenes, H. influenzae, and at least 95% S. pneumoniae isolates, makes cefditoren an antibiotic that will play a significant role in the treatment of respiratory tract infections in the community. In the clinical setting, studies carried out with cefditoren showed that treatments with the 400 mg twice daily regimen were associated with high rates of bacteriological response, even against penicillin-nonsusceptible S. pneumoniae, with good correlation between bacteriological efficacy/response and clinical outcome.Keywords: cefditoren, Streptococcus pyogenes, Haemophilus influenzae, Streptococcus pneumoniae, community-acquired respiratory tract infections